4 - A propos du plan de Lagos: Sur la science et la technologie - Fayqal YACHIR, (Africa Development, 1982)
The author argues that , on science and technology policy , the Lagos Plan is unrealistic and contradictory . It is unrealistic not in the sense of being Utopian , but in so far as it does not define any serious priority, neither for the objectives to be pursued nor for the means to be used . It is contradictory because of a deep inadequacy between its overall aim of an autonomous development of African economies and the industrial and technological model it suggests implicitly . Thus, the objective of self-reliant development is contrasted to the model of industrial growth which is recommended by the Lagos Plan, and which appears to be centered around a basic-needs capitalist strategy, leaving unresolved the question of capital goods production . Then the objective of a technological autonomy is contrasted more specifically to the policies suggested by the Lagos Plan in relation to the forms of technology imports and to the social and eco-nomic nature of the techniques to be bought and/or generated locally. Fayçal YACHIR, CREA - Algérie.